Impacts of climate change and human activities on vegetation coverage variation in mountainous and hilly areas in Central South of Shandong Province based on tree-ring - Yin, Tingting; Zhai, Yinuo; Zhang, Yan; Yang, Wenjun; Dong, Jinbin; Liu, Xiao; Fan, Peixian; You, Chao; Yu, Linqian; Gao, Qun; Wang, Hui; Zheng, Peiming; et al. (Frontiers in Plant Science, 2023)
It is of great significance to understand the characteristics and influencing factors of vegetation coverage variation in the warm temperate zone. As a typical region of the warm temperate zone in eastern China, the mountainous and hilly region in central-south Shandong Province has fragile ecological environment and soil erosion problem. In this study, the vegetation coverage from 1905 to 2020 was reconstructed based on tree rings and the normalized vegetation index (NDVI), which can represent the vegetation coverage. In the reconstructed sequence, 23 years had high vegetation coverage and 15 years had low vegetation coverage. After low-pass filtering, the vegetation coverage of 1911–1913, 1945–1951, 1958–1962, 1994–1996, and 2007–2011 was relatively high, while the vegetation coverage of 1925–1927, 1936–1942, 2001–2003, and 2019–2020 was relatively low. Although precipitation determined the variation of vegetation coverage in this study area, the impacts of human activities on the change of vegetation coverage in the past decades cannot be ignored. With the development of social economy and the acceleration of urbanization, the vegetation coverage declined. Since the beginning of the 21st century, ecological projects such as Grain-for-Green have increased the vegetation coverage. These findings will help to understand the relationship between climate change and vegetation coverage variation in warm temperate regions of eastern China, and to better understand the impacts of human activities on vegetation cover dynamics.